Estimating Company Value Considering its Future Risk Before IPO of PT Karya Internusa: A Construction Company - Wiryono, Sudarso Kaderi; Putri, Fawwaz Lu’ay (Journal of Business and Management, 2014)
In the last decades, the development in economy of Indonesia has been growing to the better stage. This development stimulates other sector to grow together. This situation attempts the company, which operates in infrastructure to compete to be the best in its business. PT Karya Internusa is a construction company who was established in 1997 and had been expand the business to batching plant sector in 2013. PT Karya Internusa specialized in construction and architecture, excavation foundation and fabrication and installation of steel construction. PT Karya Internusa has done many projects from big companies like Pertamina, PLN, Wilmar Indonesia, Petrokimia Gresik, etc. that makes the revenue of the company that has been growing in last few years and they always want to improve it since they want to being IPO (Initial Public Offering) in next five years. But, before that the company should know what are their future risk in order to estimate how much their value and what are the action required in order to increase the company value. Qualitative Method is used to measure the risk and Discounted Free Cash Flow approach is also used to determine the company value with considering the future risk. In conclusion, the range of PT Karya Internusa’s value is IDR 220,138,861,481 to IDR 290,171,426,063. However, the company should do the risk mitigations, increase and maintain the future growth and reduce the cost of financing. It will help PT Karya Internusa to increase its value.Keywords: Value, valuation, future risk, initial public offering (IPO)